Introduction to remote sensing - Cracknell, Arthur 1940- (Taylor & Francis, 1991)
"Addressing the need for updated information in remote sensing, Introduction to Remote Sensing, Second Edition provides a full and authoritative introduction for scientists who need to know the scope, potential, and limitations in the field. The authors discuss the physical principles of common remote sensing systems and examine the processing, interpretation, and applications of data. This new edition features updated material, including greater coverage of applications from across earth, environmental, atmospheric, and oceanographic sciences. Illustrated with remotely sensed color images from satellites and aircraft, it also outlines data acquisition and analysis."--Jacket. "The authors discuss the physical principles of common remote sensing systems and examine the processing, interpretation, and applications of data. This new edition features updated material, including greater coverage of applications from across earth, environmental, atmospheric, and oceanographic sciences. Illustrated with remotely sensed color images from satellites and aircraft, it also outlines data acquisition and analysis."--BOOK JACKET.